Numerical representation of topological real algebras - Mendes, S.; Bettencourt, G. H. (Revista Colombiana de Matemáticas, 2023)
We show that the isomorphism provided by the Gelfand-Mazur theorem for a commutative pre-ordered real Banach algebra A with unit defines a numerical representation which is compatible with the order structure.